Witraż świecki i kościelny: sens i walor - Henryk Nadrowski (Studia Theologica Varsaviensia)
In the modern world, so strongly surrounded by sound, light and colour, it is worth to notice their impact on various fields of our everyday life and celebrating. The multicoloured play in the sun is a phenomenon of stained glass windows. They enliven our life, stimulate imagination, encourage reflection, meditation and even contemplation. Secular stained glass windows usually show the beauty of nature, for example: flowers, but also heraldic themes, or portraits. In an object of worship it should be decided whether or not a stained glass window should be placed. The stained glass cannot be treated only as a decoration or an extra under any circumstances. It should refer to the title or dedication of the particular church. It is advisable to reach for Christian symbolism or iconography, the message of Bible and the spirit of liturgy celebrated. It is the stained glass itself that has to contribute to the atmosphere of prayer, to increase integrity, sense and dignity of a sacred object. Naturally, the proper quality of the stained glass windows should also be helpful.